Holding Gains and Losses as Cost Savings: A Comment on Supplementary Statement No. 2 on Inventory Valuation. - Petri, Enrico (The Accounting Review, 1973)
This article presents a comment on Supplementary Statement No. 2 on inventory valuation. The majority of the Committee on Inventory Measurement supported the replacement cost approach as the best of several available inventory measurements. Focusing the attention of users on "management's success or failure" seems to imply that holding activity is to be used as a surrogate of performance in the inventory area. In the presence of uncertainty, speculation by management about future price movements can prove to be "dangerous." One suspects that the Committee perceived that the risk of a price decline would act as a brake on unbridled speculation, whereas the reporting of holding gains would act to encourage inventory investment when price increases were reasonably evident. Since the methods recommended by the Committee do not establish standards for evaluating the magnitude of holding gains and losses, purchasing management could be encouraged to satisfice rather than maximize their reported performance with respect to discretionary purchases. The Committee concluded its report with the suggestion that two specific methods of replacement costing be used in the belief that these methods would portray the effects of their recommendation on financial reports.